A new method for quantifying causative and diagnostic markers of methylenecyclopropylglycine poisoning. (2019) - Sander, Johannes; Terhardt, Michael; Sander, Stefanie; Aboling, Sabine; Janzen, Nils
Graphical abstract: Highlights: Quantification of methylenecyclopropylglycine by tandem mass spectrometry. Combined measurement of acyl compounds and toxins of Sapindaceae . Rapid diagnosis of soapberry poisoning by serum and urine analysis. Abstract: Background: Up to now quantification of hypoglycin A in serum and urine in the range of nmols to μmols per liter plus the measurement of accumulated acyl conjugates have been used for the diagnosis of poisoning by fruits or seeds of Sapindaceae in humans and animals. A second poison, methylenecyclopropylglycine, however, is known to occur in this material. The objective of our study was to develop and evaluate a method for the quantification of this compound suitable for test materials obtained from animals and man. Method: Methylenecyclopropylglycine was extracted from serum and urine of a volunteer by a methanolic solution containing labeled methylenecyclopropylglycine as internal standard. UPLC-MS/MS analysis was performed after butylation. Results: Lower limits of detection and quantification were found at 0.5 and 2.5 nmol/L respectively in both urine and serum for each of two isomers, linearity of results (r 2 > 0.998) was demonstrated for the range of 0.5–500 nmol/L in urine and serum. The method was applied to urine and serum of horses poisoned by Acer seeds, methylenecyclopropylglycine was found in addition to hypoglycin A. Methylenecyclopropylformyl glycine, a metabolite of methylenecyclopropylglycine, however, was present in much higher concentrations than methylenecyclopropylglycine in all but one samples. Conclusions: Quantification of methylenecyclopropylglycine can be successfully integrated into our established analytical procedure used for clinical diagnosis of Sapindaceae poisoning. The extended method will improve disease evaluation in humans and animals.